Neurodevelopmental disorder risk in babies with history of hyperbilirubinemia - Baginda Hutahaean; Alifiani Hikmah Putranti; Kamilah Budhi Rahardjani (Indonesian Pediatric Society, 2008)
Background Neurodevelopmental disorder (ND) is defined asfailure to attain normal neurological function. Indirect bilirubinhas essential role because its neurotoxic properties. Neonates withhyperbilirubinemia carry the risk to develop ND.Objective To determine the association between neonatal indirecthyperbilirubinemia and the risk of ND.Methods Neonates with indirect serum bilirubin (SIB) level >10mg/dL, admitted in the period of October 2004-August 2005, wereincluded in this study. They were followed-up and screened usingBayley Infant Neurodevelopmental Screener (BINS) at three, sixand nine months. Mann-Whitney test was used to test thehypothesis.Results Forty-eight neonates were included in the study. MeanSIB level of subjects with ND risk was 20.5 mg/dL (SD=6.06;p<0.001). Mean SIB level of subjects who developed ND at three,six and nine months was 31.6 mg/dL (SD=4.02), 18.4 mg/dL(SD=2.92) and 18.4 mg/dL (SD=5.41), respectively. There wasstatistically significant correlation between SIB level and NDrisk (R=+0.64; P<0.001). There was also statistically significantcorrelation between SIB level and the onset of ND (R=-0.63;P< 0.001).Conclusion There is a correlation between neonatal SIB leveland the risk of ND in babies.